Prevalence of the most common psychological problems duringcoronavirus epidemics: A systematic review and meta-analysis - Pourdehghan, Parandis; Mohammadi, Mohammad Reza; Mostafavi, Seyed-Ali (Current Problems of Psychiatry, 2022)
Introduction. There have been so far three noteworthy epidemics caused by coronaviruses: SARS, MERS, and COVID-19. We aimed to review prevalence of the most common psychological problems during these epidemics.Material and methods. We conducted systematic reviews and meta-analyses of studies. A comprehensive search was performed in electronic databases PubMed/MEDLINE, Web of Science, PsycINFO/ProQuest, SCOPUS, and Google Scholar. Two independent reviewers searched for all English-language articles on psychological problems during coronavirus epidemics published by February 2021. We used DerSimonion-Laird random-effects model to estimate the prevalence of psychological problems. We conducted subgroup analyses to analyze the source of heterogeneity. Meta-regression model was also used.Results. Eighty-eight eligible papers were included. The prevalence of the most common psychological problems was insomnia (27%), depression (24.8%), stress (22%), and anxiety (12.4%), respectively. Subgroup analysis indicated that healthcare workers were more likely to have the mentioned psychological problems compared to survivors and the general population. According to meta-regression analyses, study tools and study populations were identified as the most important sources of heterogeneity. Variability in study tools and study populations was attributed to a high level of heterogeneity.Conclusions. This study suggested that people during coronavirus epidemics were exposed to insomnia, depression, stress, and anxiety far more than other psychological problems.